Aspiration and Inspiration: Using Bronchoalveolar Lavage for Toxicity Assessment. (February 2021) - Poitout-Belissent, Florence; Grant, Shawn N.; Tepper, Jeffrey S.
Bronchoalveolar lavage (BAL) is a simple procedure that is used to investigate drug efficacy or lung toxicity. It is sensitive to lung changes and less invasive than histological evaluation. It can be performed repeatedly at interim time points or as a terminal procedure. Airborne contaminants and purposely inhaled compounds, resident and inflammatory cells, as well as different cellular soluble products can be harvested in bronchoalveolar fluid (BALF) and measured. Bronchoalveolar lavage can also be an important tool to understand drug exposure and its metabolism in the lung, although it should be rigorously performed and interpreted with caution, especially in the context of regulated toxicology studies. This review focuses on the methods and uses of BAL in animal research, primarily in the pharmaceutical industry, as well as for the assessment of drugs, pollutants, and chemical lung toxicity. Methods of collecting and analyzing BALF and parameters affecting variability are discussed in detail. Improved automated methods for cell counting and analysis of the inflammatory cellular differential using hematology analyzers, common markers of lung injury, and new methodologies are described. Correlation between BALF and histological evaluation should not be considered as repetitive but as complementary assessments in the context of efficacy and toxicity studies.